Identification of Infrastructure Facilities of Senior Kindergarten Institutions in the Readiness of Special Education of Jogjaan - Pamungkas, Joko; Sudaryanti, Sudaryanti; Rolina, Nelva; Agustiningsih, Rini (Journal of Social Science and Education Research, 2024)
This study aims to identify the facilities and infrastructure of kindergarten institutions in the readiness of typical education in Jogja. The research method used is a survey involving kindergarten institutions in the Special Region of Yogyakarta. The data collection technique is carried out by filling out the questionnaire that has been given and then analyzed using descriptive quantitative data. The results of the study show that as many as 65% of institutions do not have facilities and infrastructure in typical Jogja education. This figure indicates that more than 50% of kindergarten institutions in the special region of Yogyakarta are not ready to implement a special education program for Jogja. Facilities and infrastructure are important factors in the implementation of typical Jogja Education, facilities and infrastructure are also the benchmark in order to be able to organize typical Jogja Education optimally.